Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1080/00423114.2015.1046460
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency vibration control of floating slab tracks using dynamic vibration absorbers

Abstract: This study aims to effectively and robustly suppress the low-frequency vibrations of floating slab tracks (FSTs) using dynamic vibration absorbers (DVAs). First, the optimal locations where the DVAs are attached are determined by modal analysis with a finite element model of the FST. Further, by identifying the equivalent mass of the concerned modes, the optimal stiffness and damping coefficient of each DVA are obtained to minimise the resonant vibration amplitudes based on fixed-point theory. Finally, a three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 28 publications
1
34
0
1
Order By: Relevance
“…It is shown that the vibration attenuation of a speci c frequency band can be achieved by the reasonable design of a dynamic vibration absorber on the basis of a oating slab track [4,[17][18][19]. Based on this idea, a oating slab track structure with an additional tuned slab damper is proposed to control the vibration of a speci c lowfrequency band.…”
Section: Track Structural Patternmentioning
confidence: 99%
“…It is shown that the vibration attenuation of a speci c frequency band can be achieved by the reasonable design of a dynamic vibration absorber on the basis of a oating slab track [4,[17][18][19]. Based on this idea, a oating slab track structure with an additional tuned slab damper is proposed to control the vibration of a speci c lowfrequency band.…”
Section: Track Structural Patternmentioning
confidence: 99%
“…Zhai et al 12 formulated the train-track-bridge interactions and provided a dynamic model to study the lateral and vertical vibrations of a train-track-bridge system. Zhu et al 13 presented a coupled dynamic model for a metro train to study the system low-frequency vibrations. Cantero and Karoumi 14 established a traintrack-bridge system model to discuss the influences of the train speed, track irregularity cases, and bridge characteristics on the system vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…This railway track model was used to study the effect of passing vehicles on pavements [11]. There are also studies devoted to the vibration monitoring and control of railway tracks [12], [13]. Track deflections induced by train passage are a cause of ride discomfort, fatigue in railway, and disturbances to nearby buildings [12].…”
Section: Introductionmentioning
confidence: 99%